The Role of Leadership, Organizational Culture, Knowledge, Attitude, and Skills in Developing Performance in Hospitals - Gifari, Zikry Mohammad; Andarusito, Nurcahyo; Rosa, Tina (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2026)
Standard operating procedures and clinical protocols do not solely determine hospital performance; it is also significantly influenced by internal organizational factors, such as leadership style and organizational culture, as well as individual factors, including knowledge, attitudes, and skills. A mixed-methods approach was employed, combining quantitative surveys with Structural Equation Modeling (SEM-PLS) and qualitative semi-structured interviews. A total of 191 nurses were selected by simple random sampling, and three key informants (a senior nurse, a junior nurse, and a nurse manager) were interviewed. Quantitative data were analyzed for validity, reliability, path coefficients, and effect sizes. Qualitative data were analyzed using thematic coding and triangulated with observation. All five variables—leadership, organizational culture, knowledge, attitudes, and skills—significantly influenced performance (p < 0.05). Leadership and skills had the largest effect sizes (f² = 0.655 and 0.798, respectively). Organizational culture, knowledge, and attitudes had smaller yet meaningful effects. The qualitative findings supported those of the quantitative data, indicating that leadership and a collaborative organizational culture enhanced motivation and coordination, thereby improving performance. These findings support integrating Human Relations Theory, Maslow’s Hierarchy of Needs, Theory X and Y, and Dual Process Theory to understand performance development in hospitals. The interplay between structural and personal factors shapes hospital performance.